Young bone marrow transplantation delays bone aging in old mice - Lina, Abu-Nada (2025)
Recent discoveries have shown that systemic manipulations, such as parabiosis, blood exchange, and young plasma transfer, can counteract many hallmarks of aging. This rejuvenation effect has been attributed to circulatory factors produced by cells from both hematopoietic and non-hematopoietic lineages. However, the specific involvement of bone marrow (BM) or hematopoietic cells in producing such factors and their effects on aging is still unclear. We developed a model of aged mice with transplanted young or old BM cells and assessed the impact on the aging process, specifically on energy metabolism and bone remodeling parameters. The donor BM cell engraftment in the aged mice was confirmed by flow cytometry using a transplanted cell-specific marker (green fluorescent protein). Energy metabolism was assessed using Oxymax indirect calorimetry system after 3 months of transplantation. Tibiae and L3-L4 vertebrae were analyzed using micro-CT, a three-point bending test and bone histomorphometry. Moreover, bone marrow proteome was assessed using proteomics, and blood serum/plasma was collected and analyzed using the Luminex assay. Our results showed that while the effect on energy metabolism was insignificant, rejuvenating the BM through young bone marrow transplantation reversed age-associated low bone mass traits in old mice. Specifically, young bone marrow transplantation improved bone trabecular microarchitecture both in tibiae and vertebrae of old mice and increased the number of osteoblasts and osteoclasts compared to old bone marrow transplantation. In conclusion, young bone marrow cells may represent a future therapeutic strategy for age-related diseases such as osteoporosis. The findings of this study provide important insights into our understanding of aging.